Verification of Cold Treatment for Postharvest Control of Ceratitis capitata (Wiedemann), Mediterranean Fruit Fly, in Three Cultivars of Table Grapes - Platt, T.B.; Johnson, S.A.; Moelich, D.H. (South African Journal of Enology and Viticulture, 2024)
Cold treatment schedules for the control of phytosanitary insect pests such as fruit flies (Tephritidae) is standard practice in the international trade of fresh agricultural products. This study presents data on the efficacy of cold treatment of three table grape cultivars artificially infested with Ceratitis capitata (Mediterranean fruit fly) larvae, and demonstrates that, irrespective of cultivar, cold treatment at 1°C or below for 16 days, will effectively mitigate the risk of C. capitata in table grapes.